Classroom Teachers' Awareness of Teaching Thinking Skills - BAYSAL, ZELİHA NURDAN (ANI PUBLISHING, 2017)
This study aims to reveal the classroom teachers' awareness of teaching thinking skills. The study was conducted as a basic interpretive qualitative research design in which we examined the awareness of teaching thinking skills among the classroom teachers working at the primary schools in the Pendik district of Istanbul by using a form including open-ended questions. The form included seven open-ended questions in total. Criterion sampling was used to select the cases. The first criterion was to have five-year experience in primary school teaching and the second one was to be able to to write down at least four thinking skills. 37 classroom teachers constituted the study group. The data were analyzed by descriptive analysis. The findings were grouped under four main categories. Key findings from the study include: Most of the classroom teachers stated that they have lower awareness that thinking skills are teachable and must be taught in lessons and they have higher awareness that thinking skills help the students in adapting to era (globalizing world). Most of the classroom teachers also stated that they have often meet with problems in teaching thinking skills.
Keywords: Skills; thinking skill; primary school; classroom teachers